Physical-hydric quality of a Regosol under integrated and conventional crop production systems - Figueiredo Neto, Nabor Galvão de; Silva, Pedro Luan Ferreira da; Oliveira, Flávio Pereira de; Martins, Adriana Ferreira; Tavares, Danillo Dutra; Campos, Milton César Costa (Revista Agrogeoambiental, 2023)
Sandy soils have gained increased attention due to the expansion of new agricultural frontiers in Brazil and worldwide, however, they are sensitive to land use changes. The objective was to evaluate the physical-hydric quality of a Regosols under integrated and conventional production systems in the climatic conditions of the semiarid domain of Paraíba, Brazil. The study was carried out in the municipality of Lagoa Seca/PB, Brazil (7°10’15” S, 53°51’43” W, and 640 m of altitude), on a Regosols with a sandy loam textural classification. The experiment was set up in an entirely randomized design, with five treatments and five repetitions. The treatments were composed of: 1) Mombaça grass (Panicum maximum Jacq.) + Maize (Zea mays L.) (M+M); 2) Urochloa decumbens (Stapf) R. D. Webster + Maize (U+M); 3) secondary forest (SF); 4) conventional agriculture area, cultivated with bean (Phaseolus vulgaris L.) (AGR); and, 5) area in regeneration stage (ARS). The following variables were analyzed: flocculation degree, clay dispersed in water, soil porosity (total, macroporosity, microporosity), aeration porosity in the macro pore domain, soil bulk density, hydraulic conductivity, and available water. According to the results, the physical-hydric quality of the soil between the integrated systems was not significant, but compared to the conventional system, it showed satisfactory results. On the other hand, it is concluded that the modification of soil structure in an agricultural area has reduced water availability to plants to 75.20% below what is considered adequate. Long-term studies should be conducted in order to verify the effect of integration systems on improving the physical and structural quality of sandy soils.